Metastatic MiT family/TFE translocation renal cell carcinoma in adults: case series reports and literature reviews - Sun, Xueru; Wang, Hong; Man, XiuYue; Chen, Chen; Cong, XiaoFeng; Zhang, Jing; Yang, Lei (Frontiers in Oncology, 2025)
This article presents a case study of three patients diagnosed with MiT/TFE tRCC at our hospital. The tumors were located in the left kidney of all three patients, with two of them being under 30 years old. Within a short timeframe, two of all patients developed liver metastases. Genetic testing was conducted in one case, FISH testing in another, and all cases underwent a combination of targeted therapy and immunotherapy. By analyzing the clinical, pathological, and genomic characteristics of these patients, this article aims to enhance the understanding of MiT family translocation renal cell carcinoma, as well as improve the diagnosis, treatment, and prognosis of this rare form of renal cell carcinoma. Further evidence is provided to support these findings.